Surveillance of invasive Aedes mosquitoes along Swiss traffic axes reveals different dispersal modes for Aedes albopictus and Ae. japonicus. - Pie Müller; Lukas Engeler; Laura Vavassori; Tobias Suter; Valeria Guidi; Martin Gschwind; Mauro Tonolla; Eleonora Flacio (Public Library of Science (PLoS), 2020)
Over the past three decades, Europe has witnessed an increased spread of invasive aedine mosquito species, most notably Aedes albopictus, a key vector of chikungunya, dengue and Zika virus. While its distribution in southern Europe is well documented, its dispersal modes across the Alps remain poorly investigated, preventing a projection of future scenarios beyond its current range in order to target mosquito control. To monitor the presence and frequency of invasive Aedes mosquitoes across and beyond the Alps we set oviposition and BG-Sentinel traps at potential points of entry with a focus on motorway service areas across Switzerland. We placed the traps from June to September and controlled them for the presence of mosquitoes every other week between 2013 and 2018. Over the six years of surveillance we identified three invasive Aedes species, including Ae. albopictus, Ae. japonicus and Ae. koreicus. Based on the frequency and distribution patterns we conclude that Ae. albopictus and Ae. koreicus are being passively spread primarily along the European route E35 from Italy to Germany, crossing the Alps, while Ae. japonicus has been expanding its range from northern Switzerland across the country most likely through active dispersal.